Temperature dependence of optical fiber current sensor with external conversion - Barczak, Kamil; Juraszek, Janusz (Photonics Letters of Poland, 2023)
The paper presents the research of a optical fiber current sensor with external conversion (OFCS-EC) as a function of temperature. The sensor was developed in the Department of Optoelectronics. The sensor was tested in the temperature range from 23 °C – 80 °C. For each of the temperatures, the sensitivity was determined on the basis of a sinusoidal waveform. Thus, the linearity of the transfer characteristics was checked. The main purpose of the experiment was to check the limits of sensitivity changes in changing thermal conditions and whether the sensor meets the standards used in the power industry. Full Text: PDF References M.J. Weber, "CRC Handbook of Laser Science and Technology. Supplement 2: Optical Materials", CRC Press, Boca Raton, FL, USA (1995). CrossRef S. Ju, Y. Lee, Y.T. Ryu, S.G. Kang, J. Kim, P.R. Watekar, B.H. Kim, Y. Lee, Y.H. An, C.J. Kim, W.T. Han, "Temperature Dependence of Faraday Rotation of Glass Optical Fibers Doped with Quantum Dots of CdSe and CdMnTe", Phys. Status Solidi A, 216: 1800549 (2019). CrossRef E. Lage, L. Beran, A.U. Quindeau, L. Ohnoutek, M. Kucera, R. Antos, S. R. Sani, G.F. Dionne, M. Veis, C.A. Ross; Temperature-dependent Faraday rotation and magnetization reorientation in cerium-substituted yttrium iron garnet thin films. APL Mater. 5, 036104 (2017). CrossRef S. Ju, J. Kim, K. Linganna, P.R. Watekar, S.G. Kang, B.H. Kim, S. Boo, Y. Lee, Y.H. An, C.J. Kim, et al. "Temperature and Vibration Dependence of the Faraday Effect of Gd2O3 NPs-Doped Alumino-Silicate Glass Optical Fiber". Sensors, 18, 988 (2018). CrossRef A. Jeffrey, D. and R.M. Bunch, "Temperature dependence of the Faraday rotation of Hoya FR-5 glass," Appl. Opt. 23, 633 (1984). CrossRef K. Barczak, J. Juraszek, "Optoelectronic system for detecting short-circuits in low voltage networks", Photon. Lett. Pol, 14, 37 (2022). CrossRef K. Barczak, K. Mazniewski, "Optical fiber current sensor with external conversion for measurements of low AC electric currents", Proc. SPIE, 10455 (2017). CrossRef